(untitled) (Journal of Geography and Environmental Management, 2019)
In this article was shown the role and importance of forest resources in maintaining the ecological and socio-economic al stability in Kyrgyzstan. Also the geographical features of the country, protection and development of forests in the region and the basic directions of their integrated use were viewed.